WAYS TO DEVELOP THE SYSTEM OF INTERNAL AND EXTERNAL FOOTBALL LEAGUES IN HIGHER EDUCATION - Babayev Anvarjon Akhmedovich (Modern American Journals, 2025)
This article analyzes the formation and development of internal and external football league systems in higher education institutions. The role of football in promoting a healthy lifestyle among students, as well as its contribution to fostering teamwork and competitiveness, is highlighted. The paper examines effective ways to organize internal leagues (inter-faculty and inter-institute) and external leagues (between universities at city, regional, or national levels), focusing on their organizational-methodological aspects, material and technical support, and management mechanisms. Furthermore, proposals are presented for enhancing students' physical and social activity through the introduction of regular football leagues. The research findings demonstrate the significance of popularizing football in higher education and creating a healthy competitive environment among youth.
Keywords: higher education, football, internal leagues, external leagues, student competitions, healthy lifestyle, sports system, physical education, competition, football clubs, sports management, youth sports